Surface Thermodynamic Gradients Associated with Gulf of Mexico Sea-Breeze Fronts - Loren D. White; Michael Koziara (Advances in Meteorology)
High spatial/temporal resolution mobile transects were used to examine the thermal and moisture structure of the sea-breeze front (SBF) along the Mississippi coast during August 2014 and 2015. Compared to most similar studies, conditions were much warmer and more humid. Results show a 1-2 g/kg increase in mixing ratio across the mature SBF zone, and up to a 2.5°C temperature decrease. When SBF radar fine lines are identifiable, their position agrees very well with surface thermodynamic changes. Although temperatures were cooler at the coast, microscale offsets in location of thermal, moisture, and radiative features are noted in the vicinity of the SBF, particularly when the sea-breeze system is relatively weak or immature. At times, it seems that strong solar insolation causes the temperature to rise temporarily within the transition zone behind the kinematic SBF. These results are at variance with most other diagnostic studies. Some thermodynamic variations are noted within the marine air mass in connection to minor water bodies such as Biloxi Bay. The potential for passage of the SBF to at least temporarily increase human heat stress as described by heat index is also noted.